The effect of nitrogen dilution and hydrogen enrichment on the explosive limits of liquefied petroleum gas (LPG) - Abdullah, Huzaifah (2010)
The aims of this study are to determine the explosive limits of LPG/ air and to investigate the effect on explosive limits of LPG/ air when addition of hydrogen and dilution of nitrogen at atmospheric pressure and ambient temperature. The purpose of diluting with nitrogen is to control the explosive limits range of LPG because hydrogen will extend the explosive limits of LPG. This is for safety to avoid the LPG become very flammable fuel but at the same time to get the best performance of fuel mixing. The experiments were performed in a 20 L closed explosion vessel. The mixtures were ignited by using a spark permanent wire that placed at the centre of the vessel. The pressure-time variations during explosions of LPG/air mixtures in explosion vessel were recorded. The explosion pressure data is used to determine the explosive limits which flame propagation is considered occurred if explosion pressure greater than 0.1 bar. From the explosion pressure data, the maximum explosion pressure is determined also. In this study, the result shows the explosive limits of LPG is from 2 vol% to 8 vol % of LPG. The addition of 2 and 8 vol% hydrogen in 7 vol% nitrogen reduce the lower explosive limit(LEL) initially 1 vol% to 0 vol% of LPG/air mixture. For safety aspect, the addition too much hydrogen seems very dangerous for application because the mixture is in very flammable condition. The dilution nitrogen seems not give effect in controlling the explosive limits in this case.